Cash holdings and R&D smoothing - Brown, James R.; Petersen, Bruce C. (Journal of Corporate Finance, 2011)
The sharp increase in R&D investment in recent decades has important but unexplored implications for corporate liquidity management. Because R&D has high adjustment costs and is financed with volatile sources, it is very expensive for firms to adjust the flow of R&D in response to transitory finance shocks. The main contribution of this paper is to directly examine whether firms use cash reserves to smooth their R&D expenditures. We estimate dynamic R&D models and find that firms most likely to face financing frictions rely extensively on cash holdings to smooth R&D. In particular, our estimates suggest that young firms used cash holdings to dampen the volatility in R&D by approximately 75% during the 1998–2002 boom and bust in equity issues. Firms less likely to face financing frictions appear to smooth R&D without the use of costly cash holdings. Our findings provide new insights into the value of liquidity and the financing of intangible investment, and suggest that R&D smoothing with cash reserves is now important for understanding cash management for a substantial fraction of publicly traded firms.